(3cJGH GdWH GdLOjO GdcjeGhis - (3HQGcdShSs
(3ChdgG (B:s
(3gPG cJGH GdWH GdLOjO GdcjeGhi GdPi bO ENJQYg HQGcdShS jTJed Ydi ebOeI hebGdGJ GdebOeI ai JYQja GdcjejGA hHjGf GdMGLI EdjgG hGdZQV efgG afbhd GdcjejGA daX jhfGf CUdg NjejG s
(3BNQgG (B:s
(3GdSDGd GdYTQhf (B: (3ce gi GdCSHGH ef bHhd GdYVh GdbGHd GdLhGH (B: (3SHYI GdChd (B: (3ELJeGY aVdg ai GdYVh GdOGaY GdSGHY Vjb GdeLGQi GdJi JOaY GdbGHd aVhdg ajgG hGddg CYde Je HYhf Gddg hMSf Jhajbg s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjf HGdMeQIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs